(untitled) (NTU Journal of Agriculture and Veterinary Science, 2025)
The study assessed the impact of ABP on rice farmers’ yield in Niger State, Nigeria. Objectives of the study are to: identify the farmers’ sources of information and determine the impact of ABP on farmers. A total of 138 farmers were randomly selected. Data was analysed using descriptive, correlation, t-test, and regression analyses. OLS result showed a significant relationship existed between beneficiaries’ farming experience (ß = 19.23, p?0.01), farm size (ß = 17.01, p?0.05), (ß = 1.07, p?0.03) and productivity. Also, there was significant difference between the beneficiaries’ productivity before and after the introduction of ABP. It was concluded that there is a causal relationship between farming experience, farm size, credit accessibility and farmers’ productivity, and that ABP had a positive effect on the rice farmers’ productivity. The study recommended that more information and enlightenment should be given concerning ABP, and that the programme should be given better supervision.